RETRACTED ARTICLE: Metagenomics for taxonomy profiling: tools and approaches. Issue 1 (1st January 2020) - Kumar Awasthi, Mukesh; Ravindran, B.; Sarsaiya, Surendra; Chen, Hongyu; Wainaina, Steven; Singh, Ekta; Liu, Tao; Kumar, Sunil; Pandey, Ashok; Singh, Lal; Zhang, Zengqiang
Statement of Retraction: We have retracted the following article: Mukesh Kumar Awasthi, B. Ravindran, Surendra Sarsaiya, Hongyu Chen, Steven Wainaina, Ekta Singh, Tao Liu, Sunil Kumar, Ashok Pandey, Lal Singh & Zengqiang Zhang, "Metagenomics for taxonomy profiling: tools and approaches, " Bioengineered, 10.1080/21655979.2020.1736238. After publication, concerns were raised about similarities between this article and the following papers: DOI: 10.1016/j.biortech.2019.01.117 DOI: 10.1016/j.jcf.2012.07.009 DOI: 10.3168/jds.2017-13356 DOI: 10.1016/j.mimet.2016.05.022 These concerns were upheld and the article is retracted. We have been informed in our decision-making by our policy on publishing ethics and integrityandthe COPE guidelines on retractions.The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as "Retracted".